Wilder’s Joyce: Inspiration, Borrowing, Appropriation, Plagiarism - Gontarski, S. E. (ABEI Journal, 2023)
American novelist and playwright Thornton Wilder’s lifelong attraction to and passion for if not obsession with the work of James Joyce has led to unintended consequences. Wilder was writing what would become his second Pulitzer Prize winning play, The Skin of Our Teeth, while in the midst of “unriddling” Joyce’s final novel, Finnegans Wake. Accusations of plagiarism would subsequently arise from two major Joyce scholars, Joseph Campbell and Henry Morton Robinson as they raised questions about the tipping point in creative practice, the point at which common practices of textual influence and reference cross the line into excessive borrowings and plagiarism. Such accusations, which Wilder failed to acknowledge and to fully address in a timely fashion, have lingered to his discredit and have obscured his achievements both as a playwright and a major scholar of experimental literature with a particular emphasis on James Joyce. The essay details the need to return to and to reassess the issues of Wilder’s creative practice within the current theoretical climate of intertextuality and thus to reassess Wilder’s pioneering work on both Ulysses and Finnegans Wake.